Rancang Bangun Otoritas Izin Masuk Pada Ruangan dengan Sistem Web Cam Face Mask Detection Dan Suhu Tubuh - Pratama, Egi Yudha; Fadli, Mohammad; Lindawati, L (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Covid-19 is a pandemic that has hit the world, including Indonesia. This pandemic can be transmitted from direct human-to-human contact. With social restrictions and also maintaining health protocols, it is felt that they can prevent the transmission of Covid-19. Areas of the face such as the mouth and nose are considered to be the fastest means of spreading. So it is necessary to use masks to reduce the spread of this pandemic. In addition, to prevent transmission a person can find out Covid-19, one of them is through body temperature. Therefore, the use of technology is considered very important in order to minimize and detect the spread of Covid-19. By using this method, it is expected to detect the use of masks and detect body temperature, in order to minimize the transmission of Covid-19 in the room.